Impact of SARS‐CoV‐2 outbreak on heart and lung transplant: A patient‐perspective survey. Issue 1 (10th August 2020) - Bennett, David; De Vita, Elda; Ventura, Vittoria; Bernazzali, Sonia; Fossi, Antonella; Paladini, Piero; Luzzi, Luca; Maccherini, Massimo; Valente, Serafina; Bargagli, Elena; Frediani, Bruno; Sestini, Piersante
Abstract: Background: The risk of COVID‐19 is expected to be higher among solid organ transplant. The aim of the present study was to evaluate the incidence of COVID‐19 and the impact of the SARS‐CoV‐2 outbreak on the personal hygiene and expectations in heart and lung transplant recipients. Methods: A telephone survey of heart (n = 69) and lung (n = 41) transplant patients and a group of controls (n = 41) was conducted concerning personal hygiene before and after the outbreak; the impact on subjective expectations regarding graft outcome; symptoms possibly associated with SARS‐CoV‐2 infection; and diagnosis of COVID‐19. Results: Seventy nine percent of the patients declared they increased the use of face masks and handwash. Behavior at home regarding self‐isolation did not change. About half the patients said they were afraid of the virus. A higher percentage of Lung transplant (LTX) were convinced that SARS‐CoV‐2 could have a negative impact on the outcome of their graft. 28% declared that they were afraid to come to the hospital for routine examinations and asked to postpone. Nine LTX and five Heart transplant (HTX) patients experienced symptoms that could have been associated with SARS‐CoV‐2 infection, but none of them underwent a nasopharyngeal swab. Only one LTX was diagnosed with the infection. Conclusions: In our study, we observed a low incidence of COVID‐19 in heart and lung transplant patients (0.9%), similar to that of the general population of our Region. Isolation measures were already observed before the pandemic and were further strengthened in most cases. Particular attention should also be paid to new psychological and physical complications indirectly linked to the COVID‐19 pandemic.